Effect of three remplissage techniques on tendon coverage and shoulder kinematics: a navigated robotic biomechanical study. Issue 1 (December 2016) - Tan, Chung; Saier, Tim; von Deimling, Constantin; Martetschläger, Frank; Minzlaff, Philipp; Feucht, Matthias; Martinez, Horazio; Braun, Sepp; Imhoff, Andreas; Burgkart, Rainer
Abstract Background In addition to Bankart repair engaging Hill-Sachs defects in glenohumeral instability have been treated successfully with remplissage procedure. The purpose of this study was to compare three remplissage techniques regarding (I) ability of preventing Hill-Sachs defect from engaging, (II) influence on glenohumeral rotational torque, and (III) resulting tendon coverage over the Hill-Sachs defect. Methods Standardized engaging Hill-Sachs defects and Bankart lesions were created inn = 7 fresh frozen human shoulder specimens. Besides Bankart repair three remplissage techniques (T) with double anchor position in the valley of the defect zone were studied: T1, knots tied over anchors; T2, knots tied between anchors (double-pulley); T3, knotless anchors with a suture tape. A parallel position-orientation and force-moment controlled navigated roboticsystem was used to compare prevention of Hill-Sachs defect engagement and torque [Nm]. Pressure sensitive film was used to study area of infraspinatus tendon coverage over Hill-Sachs defect [%]. Results All remplissage techniques prevented engagement of the Hill-Sachs defect without showing any construct failures. Regarding humeral torque there were significant impairments observed between intact conditions and the three investigated repair techniques in 60° abduction and ≥30° external rotation (p < .04). There was no significant difference in torque between intervention groups (n.s.). With a mean coverage of 26.8 % over the defect zone the knotless suture tape technique (T3) significantly improved area of soft tissue coverage compared to the other techniques (p = .03). Conclusion All remplissage techniques prevented engagement of the Hill Sachs defect. With high abduction and external rotation ≥30° all techniques showed significant higher humeral torque compared to the intact specimens, while there was not one technique superior over the others. The suture tape technique conferred the largest and most effective area of tendon coverage over the Hill-Sachs defect zone. Long-term success of the remplissage procedure can possibly be enhanced by increasing the interface area of tendon coverage over the Hill-Sachs defect. Clinical studies will be necessary to proof potential benefits for clinical outcome.